Primary Endoscopic Closure of Duodenal Perforation Secondary to Biliary Stent Migration: A Case Report and Review of the Literature - Samson Ferm MD; Constantine Fisher MD; Akil Hassam MD; Moshe Rubin MD; Sang-Hoon Kim MD; Syed Ahsan Hussain MD (SAGE Publishing, 2018)
Duodenal perforation due to biliary stent migration is rare, and it often requires surgical repair; however, endoscopic closure has recently become a viable option in the appropriate patients. We present the case of a 79-year-old female who underwent biliary stent placement for a common bile duct stricture, who subsequently was found to have a duodenal wall perforation secondary to stent migration. The stent was extracted endoscopically with successful defect closure using a ConMed ® repositional DuraClip™. We aim to contribute to the limited body of literature that describes endoscopic repair of duodenal perforation secondary to biliary stent migration using through-the-scope endoclips.